The Existence of Slang and the Erosion of Indonesian National Language Identity Among University Students - Lastiur sipahutar; Grace Cristina Siahaan; Intan Sukmawati Siburian; Daulat Nathanael Banjarnahor (Young Journal of Social Sciences and Humanities, 2026)
This study aims to examine the phenomenon of slang usage on social media within an academic campus environment. Employing a phenomenological approach, this research focuses on active undergraduate students at Universitas HKBP Nommensen Pematangsiantar. Data were gathered through field observations, in-depth interviews, and documentation. The findings indicate that slang is widely adopted because it is perceived as more intimate, accessible, and effective in facilitating peer comprehension, particularly during digital interactions. However, this phenomenon also indicates a linguistic shift that potentially marginalizes language politeness and ethics when used in inappropriate contexts. Therefore, the preservation of standard Indonesian and indigenous languages must be maintained within academic settings, whereas slang should be restricted to informal or non-academic domains. The implications of this study underscore the necessity of fostering register awareness among students. Ultimately, students are expected to develop code-switching competence based on the interlocutor and communicative setting, thereby preserving the identity and prestige of the national language on campus without impeding their communicative creativity in public spheres or social media.